Adrenergic activation attenuates astrocyte swelling induced by hypotonicity and neurotrauma. Issue 6 (28th March 2016) - Vardjan, Nina; Horvat, Anemari; Anderson, Jamie E.; Yu, Dou; Croom, Deborah; Zeng, Xiang; Lužnik, Zala; Kreft, Marko; Teng, Yang D.; Kirov, Sergei A.; Zorec, Robert
Abstract : Edema in the central nervous system can rapidly result in life‐threatening complications. Vasogenic edema is clinically manageable, but there is no established medical treatment for cytotoxic edema, which affects astrocytes and is a primary trigger of acute post‐traumatic neuronal death. To test the hypothesis that adrenergic receptor agonists, including the stress stimulus epinephrine protects neural parenchyma from damage, we characterized its effects on hypotonicity‐induced cellular edema in cortical astrocytes by in vivo and in vitro imaging. After epinephrine administration, hypotonicity‐induced swelling of astrocytes was markedly reduced and cytosolic 3'‐5'‐cyclic adenosine monophosphate (cAMP) was increased, as shown by a fluorescence resonance energy transfer nanosensor. Although, the kinetics of epinephrine‐induced cAMP signaling was slowed in primary cortical astrocytes exposed to hypotonicity, the swelling reduction by epinephrine was associated with an attenuated hypotonicity‐induced cytosolic Ca 2+ excitability, which may be the key to prevent astrocyte swelling. Furthermore, in a rat model of spinal cord injury, epinephrine applied locally markedly reduced neural edema around the contusion epicenter. These findings reveal new targets for the treatment of cellular edema in the central nervous system. GLIA 2016;64:1034–1049 Main Points: Epinephrine reduces hypotonic astrocyte swelling in vitro and in vivo. Cell swelling reduction involves cAMP‐mediated Ca 2+ hypoexcitability. Epinephrine reduces trauma‐induced astrocyte swelling; a new possibility for the treatment of cellular edema.